Assessing production-based and consumption-based greenhouse gas emissions in the Kingdom of Saudi Arabia: insights for mitigation and policy - Almutairi, Kamel (Frontiers in Environmental Science, 2025)
Greenhouse gas (GHG) emissions, and in particular CO2, are critical drivers of climate change, necessitating coordinated global efforts to mitigate their impact. This has led the Kingdom of Saudi Arabia (KSA) to launch several ambitious initiatives to curb its own emissions. However, there remain significant challenges when it comes to measuring outcomes, due to uncertainties in the existing methods and data. This current study therefore employs Production-Based (PB) and Consumption-Based (CB) emission accounting methods for KSA, emphasizing strategies to minimize the uncertainty inherent in these models. The results reveal that KSA is a net carbon exporter, with PB emissions (523 million tonnes CO2 equivalent (CO2e)) exceeding CB emissions (471 million tonnes CO2e). In addition, the validity of the applied methodology is supported by the literature. This research finds that private households form the largest contributors, along with sectors including electricity, land transport, water, and construction, as well as chemical, rubber, and plastic. The findings also confirm the potential for targeted policies to reduce emissions, i.e., the promotion of energy-efficient appliances, enhanced home insulation, public transportation, and recycling. Furthermore, this study highlights the importance of national investment in the accurate measurement of emissions and detailed energy statistics.